2017
DOI: 10.1186/s12866-017-0932-7
|View full text |Cite
|
Sign up to set email alerts
|

ChMob2 binds to ChCbk1 and promotes virulence and conidiation of the fungal pathogen Colletotrichum higginsianum

Abstract: BackgroundMob family proteins are conserved between animals, plants and fungi and are essential for the activation of NDR kinases that control crucial cellular processes like cytokinesis, proliferation and morphology.ResultsWe identified a hypomorphic allele of ChMOB2 in a random insertional mutant (vir-88) of the hemibiotrophic ascomycete fungus Colletotrichum higginsianum. The mutant is impaired in conidiation, host penetration and virulence on Arabidopsis thaliana. ChMob2 binds to and co-localizes with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…In eukaryotic organisms, reversible protein phosphorylation by protein kinases is involved in the regulation of various growth and developmental processes and responses to environmental stimuli ( Serrano, 1996 ). Protein kinase genes, ChCBK1 ( Schmidpeter et al, 2017 ) and ChMK1 ( Wei et al, 2016 ), were important for plant infection in C. higginsianum . In this study, the deletion of serine/threonine kinase ChSAT4 resulted in various defects in C. higginsianum , including the reduction of vegetative growth, stress response, K + accumulation, cell wall integrity, and pathogenicity in C. higginsianum .…”
Section: Discussionmentioning
confidence: 99%
“…In eukaryotic organisms, reversible protein phosphorylation by protein kinases is involved in the regulation of various growth and developmental processes and responses to environmental stimuli ( Serrano, 1996 ). Protein kinase genes, ChCBK1 ( Schmidpeter et al, 2017 ) and ChMK1 ( Wei et al, 2016 ), were important for plant infection in C. higginsianum . In this study, the deletion of serine/threonine kinase ChSAT4 resulted in various defects in C. higginsianum , including the reduction of vegetative growth, stress response, K + accumulation, cell wall integrity, and pathogenicity in C. higginsianum .…”
Section: Discussionmentioning
confidence: 99%
“…MOB proteins have been determined to function as co‐activators of NDR kinases in several biological systems (Komarnitsky et al ., ; Mah et al ., ; Weiss et al ., ; Hou et al ., ; Bichsel et al ., ; Bothos et al ., ; He et al ., ; Shi et al ., ; Schmidpeter et al ., ). Phosphorylation state has been shown to regulate the activity of both the kinase and its co‐activator (Millward et al ., ; Mah et al ., ; Tamaskovic et al ., ; He et al ., ; Seiler et al ., ; Wei et al ., ; Praskova et al ., ; Bao et al ., ; Ziv et al ., ; Gutiérrez‐Escribano et al ., ; Ziv et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…They have been determined to act as activating subunits and control crucial cellular processes such as mitosis, cell death, proliferation and morphology (Hergovich, ). In filamentous fungi, some MOB proteins have been shown to be essential for sexual development, hyphal fusion and pathogenicity (Maerz et al ., ; Bernhards and Pöggeler, ; Schmidpeter et al ., ). Neurospora crassa has four MOB proteins, two of them, MOB2A (NCU03314.7) and MOB2B (NCU07460.7), are functionally similar.…”
Section: Introductionmentioning
confidence: 97%
“…An example of convergent discoveries by using At MT in Colletotrichum species has been the recent independent identification of T-DNA insertional mutants in the same signaling pathway in C. higginsianum [ 87 ] and C. orbiculare [ 88 ]. Both studies found insertions in components of the Regulation of Ace2 and Cellular Morphogenesis (RAM) pathway, a complex of two kinases and associated proteins that controls cell morphology in fungi.…”
Section: Fungal Species and Biological Questions In Which Amentioning
confidence: 99%